BASIC CONCEPTS IN GEODESY AS AN INPUT FOR ADEQUATE TREATMENT OF GEOSPATIAL INFORMATION - Moya-Zamora, Jorge (2017)
Geodesy as the science responsible for the study of the Earth including its shape, size, gravity field and representation has needed and currently needs modern systems and frames of reference that can link the information resulting from measurements made. It wants to show a series of fundamental concepts mainly linked with reference systems, reference frames, geodetic datum, types of coordinates and map projection in order to establish, without going into extensive mathematical derivations, a general basis of definitions that allow users and professional linked to other geosciences have a friendly reference. Special consideration on the Sistema Geocéntrico para las Américas (SIRGAS), its role and importance as the geodetic project of greater technical impact on Latinamerica is also done. Today Costa Rica has more than ten continuously operating GNSS stations duly integrated to SIRGAS, whose geocentric coordinates constitute the geodesic basis of greater accuracy of the country.